Um pedaço da África do outro lado do Atlântico: o terreiro de candomblé Ile Iya Mi Osun Muiywa (Brasil) - Domingues, Petrônio (Diálogos Latinoamericanos, 2007)
The purpose of this article is to draw a brief historical draft of one important São Paulo candomblé cult house, the Ile Iya Mi Osun Muiywa, pointing out its principal initiatives on the religious, social, political and cultural field. This cult house’s history is mixed up with the consolidation of the candomblé in São Paulo itself. Its objective is also to point out the fact that this cult house has distinguished itself in the fight for the the povo de santo’s civil rights defense and for the end of the religious intolerance in Brazil.